Perception of natural habitat changes of West African marine protected areas. (1st April 2020) - Failler, Pierre; Touron-Gardic, Grégoire; Sadio, Oumar; Traoré, Marie-Suzanne
Abstract: The evolution of marine protected areas (MPAs) in West Africa is reviewed through a survey of managers' perception carried on between 2017 and 2018 for the establishment of the baseline of MPAs of the Network of Marine Protected Areas of West Africa (RAMPAO). Managers report that all natural habitats are subject to surface area losses. The most affected habitats were beaches, mudflats and estuarine channels, caused by erosion and rainfall deficit. Seagrasses, rocky bottoms and coral reefs also seem to be affected, but as they are not monitored and as the managers' knowledge is poor toward these habitats, changes are not properly recorded. Despite some damages, coastal forests seem to be the only natural habitat that see positive changes, mainly due to regular reforestation activities. Comparing managers' perception to scientific papers using satellite imagery shows that their judgement is similar for some habitats (beaches and forests), although there are some differences between their perception and scientific analyses about mangroves changes and even between scientific analyses themselves. However, managers' understanding of impacts coming from human activity and climate change is not strong enough. Consequently, these threats were impossible to quantify from this perception survey. Finally, there is a lack of GIS data within the MPAs. Highlights: Main natural habitats in west african MPAs are losing surface, according managers. The beach areas, mudflats and estuarine channels are the most exposed habitats. Only forests appear to be generally positive, due to reforestation activities. Seagrasses, rocky bottoms and coral reefs are barely monitored. Perceptions partly differ from satellite analyses, while located data are lacking.